The Concept of Neuroagents in Hospitality Industry and Tourism - KOZLOV, Dmitry Aleksandrovich (Journal of Environmental Management and Tourism; Vol 8 No 4 (2017): JEMT Volume VIII Issue 4(20) Summer 2017DO - 10.14505//jemt.v8.4(20).12, 2017)
This study is aimed to develop a modern concept for forecasting in hospitality industry and tourism. Methods/Analysis: In this paper it is studied a current researches in neural network’s technology and its implementation in hospitality and tourism.  It is important to understand that classical methods of data analysis nowadays are not able to make best results. There is a need to combine them to some elements of artificial intelligence. Hospitality industry and tourism paid great attention to the implementation of neural network applications in the analysis and forecasting. Modern economy is very susceptible to the influence of many factors which complicates the application of classical statistical procedures; neuroagent is a complex method of forecasting and decision-making and can be a good solution in the analysis of hidden relationships and the search for optimal response to emerging threats in hospitality and tourism. This study can be used as a concept for creation of some decision-making systems in hospitality and tourism or early warning systems.